2021
DOI: 10.1177/0954405421991418
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven multi-criteria decision-making approach for assessing new product conceptual designs

Abstract: The surge in competition among companies to acquire a more significant portion of the market as well as respecting customer preferences in high quality and diverse products result in a reduction of product life cycles. Accordingly, companies are under enormous pressure to introduce new high quality and diverse products on time. Assessing new product designs at the primary phases of new product development (NPD) is a necessary and complex activity that can considerably reduce the time and cost of introducing ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Other applications support the concept phase by providing suggestions for later manufacturing strategies [30], manufacturing capabilities [31,32], and assembly [33]. Additionally, product configurations [34,35] and product family management [36] have been explored as use-cases as well as concept analyses [37][38][39][40]. There are also attempts to influence product reliability during system design using test and field data [41].…”
Section: System Designmentioning
confidence: 99%
“…Other applications support the concept phase by providing suggestions for later manufacturing strategies [30], manufacturing capabilities [31,32], and assembly [33]. Additionally, product configurations [34,35] and product family management [36] have been explored as use-cases as well as concept analyses [37][38][39][40]. There are also attempts to influence product reliability during system design using test and field data [41].…”
Section: System Designmentioning
confidence: 99%
“…Step 2 The matrix A = (a ik ) m×m gives the difference matrix D = (d ik ) m×m by Eqs. (11) and (12).…”
Section: Product Concept Evaluation Weights Combined With Pfahp Pfahp...mentioning
confidence: 99%
“…Extensive research on decision making for conceptual design has found that Jing and others 6 and others have summarised MCDM methods for conceptual solutions into three types, one is to build pairwise comparison matrices to obtain the weights of evaluation criteria by calculation, for example, BWM (Best Worst Method) 7 and AHP (Analytic Hierarchy Process) 8 can deal with the extent to which different assessment criteria influence each other, but are susceptible to the subjective preferences of decision makers. The alternate approach is to combine the assessment figures across various criteria to generate a summed assessment value for each assessment option, and to calculate the combined indicator values to derive the option ranking results, like VIKOR (Vlsekriterijumska Optimizacija I Kompromisno Resenje) 9 , 10 and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) 11 , this type of method does not capture the impact of each evaluation criterion on the overall design. The third type is characterised by an order of preference, which identifies the strengths and weaknesses of different solutions to arrive at the best solution, such as ELECTRE (Elimination Et Choix Traduisant La Realité) 12 and PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation) 13 , 14 , but they cannot deal directly with uncertainties and have limitations in solving realistic decision problems.…”
Section: Introductionmentioning
confidence: 99%
“…MCDM methods are employed for various reasons to provide complex problems with an answer considering the userdefined preferences and criteria [40][41][42][43]. AHP, the most well-known MCDM method, is a simple-to-use, flexible and efficient one due to the fact that it has basic mathematical expressions [44] and is able to execute both quantitative and qualitative criteria by changing comparison matrix values of priorities to obtain more precise results.…”
Section: Ahp and Fahpmentioning
confidence: 99%